Photochemistry Aspects of the Laser Pyrolysis Addressing the Preparation of Oxide Semiconductor Photocatalysts - R. Alexandrescu; I. Morjan; F. Dumitrache; M. Scarisoreanu; I. Soare; C. Fleaca; R. Birjega; E. Popovici; L. Gavrila; G. Prodan; V. Ciupina; G. Filoti; et al. (International Journal of Photoenergy)
The laser pyrolysis is a powerful and a versatile tool for the gas-phase synthesis of nanoparticles. In this paper, some fundamental and applicative characteristics of this technique are outlined and recent results obtained in the preparation of gamma iron oxide (γ-Fe2O3) and titania (TiO2) semiconductor nanostructures are illustrated. Nanosized iron oxide particles (4 to 9 nm diameter values) have been directly synthesized by the laser-induced pyrolysis of a mixture containing iron pentacarbonyl/air (as oxidizer)/ethylene (as sensitizer). Temperature-dependent Mossbauer spectroscopy shows that mainly maghemite is present in the sample obtained at higher laser power. The use of selected Fe2O3 samples for the preparation of water-dispersed magnetic nanofluids is also discussed. TiO2 nanoparticles comprising a mixture of anatase and rutile phases were synthesized via the laser pyrolysis of TiCl4- (vapors) based gas-phase mixtures. High precursor concentration of the oxidizer was found to favor the prevalent anatase phase (about 90%) in the titania nanopowders.